Pengaruh Dana Pihak Ketiga (DPK) dan Non Performing Financing terhadap Profitabilitas Pada Bank Syariah Indonesia Periode 2015-2022 - Cindi Vatika Sari BR Sitanggang; Sri Fitri Wahyuni (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This research aims to determine the effect of third party funds and non-performing financing on profitability at Bank Syariah Indonesia for the period 2015 - 2022. The method used is a quantitative research method. The population in this study used financial reports at Bank Syariah Indonesia. Meanwhile, the sampling technique uses purposive sampling, which is a technique used based on predetermined criteria, namely 32 samples, starting from the first quarter of 2015 to the fourth quarter of 2022. The data used in this research is secondary data, namely the financial reports of Islamic Banks. Indonesia, accessed via the official link: https://ir.bankbsi.co.id. The data is processed using the help of a statistical application, namely SPSS. The research results show that third party funds (DPK) have a significant positive influence on profitability, while non-performing financing (NPF) has a negative influence on profitability (ROA). Simultaneously, third party funds and non-performing financing have a significant positive influence on profitability